KAJIAN YURIDIS TINDAK PIDANA PENCURIAN OLEH ANAK BERDASARKAN UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK (Studi Kasus Putusan Pengadilan Negeri Sleman Nomor 25/Pid.Sus-Anak/2018/PN.Smn) - YUWANA W, A. ENDRATA (Dinamika Hukum, 2019)
The purpose of this research is to examine and analyze the settlement of criminal acts of theft committed by children under Law No. 11 of 2012 on the Child criminal justice system. Reviewing and analyzing the judgment of judges in breaking the criminal acts of theft committed by children at the decision of the District Court of Sleman No. 25/Pid. Sus-Child/2018/PN.Smn. The Child criminal justice system is a judicial system that prioritizes children's interests. Article 7 paragraph (2) of Law No. 11 of 2012 on the Child criminal justice system, versioned in the case of a criminal offence committed by a child is threatened with imprisonment under 7 (seven) years and is not a repetition of a criminal offence. The method of approach in writing is normative juridical. The specification of this research uses analytical descriptive. The data source uses secondary data. Data collection techniques using library studies. The data analysis technique using silogism deductive logic is based on the submission of the major premise (a general statement) and then proposed a minor premise (special), from both premises then withdrawn a conclusion or conclusion.. Based on the results of the study obtained the conclusion that the case of the criminal act of theft which was sent at the District Court of Sleman No. 25/Pid. Sus-Child/2018/PN. SMN, the application of the Elements of section 363 paragraph (1) of the 3rd and 4th Books of the law Criminal Law on the theft of criminal acts of incrimination by the child is not in accordance with Law No. 11 of 2012 on the Child criminal justice system. Although it is true in the criminal acts elements of article 363 paragraph (1) of the 3rd and 4th Book of Criminal Code on criminal acts of theft with the incriminated circumstances committed by the child are fulfilled, but it is less in accordance with Article 5 paragraph (1) Law No. 11 year 2012 on the Child criminal justice system which prioritizes the justice Restorative approach. The principle of restorative justice by giving an opportunity to the perpetrators of the criminal (his family) to be responsible for redeeming his mistake by replacing the crime caused by a criminal offense committed by the child to the victim of criminal acts. Judgment of judges in breaking the criminal acts of theft committed by the child at the decision of the District Court of Sleman No. 25/Pid. Sus-Child/2018/PN. SMN is based on the description of witnesses, evidence tools, defendant's indictment, prosecutors Public prosecutor and the results of Community research by public guidance from the BAPAS and Law No. 11 of 2012 on the Child criminal justice system. Keyword: theft criminal, child criminal justice system.